Hell and Suffering In Matthew 23:33: Comparison Study Of The Concept Of Hell And Suffering In The Bible And Quran - Tangkudung, Clarry Paul (Klabat Theological Review, 2021)
This research employs qualitative research method. Hell, and suffering are two topics that mentioned many times in the Bible. these topics are discussed in detail in the Quran. There are some similarities as well as differences of understanding regarding the concept both topics. The concept of fire as the punishment element is mentioned in both scriptures. Suffering is the concept in which highly connected to the concept of punishment in the Bible and Quran. Bible and Quran remarks the concept of Hell in its narrations. Jesus mentions the word “Hell” in Matthew 23:33. The reference is pointed to the Pharisess. This word has plentiful meaning and understanding. Both scriptures mentioned the person who will bring deliverance to the people from hell and suffering. The Bible says it clearly the person who will save people from the punishment of hell. The concept of Hell is related to the concept of suffering in the Bible and in Quran. Keywords: Bible, Judge, Hadith, Hell, Heaven, Paradise, Suffering, Quran